Feminist Theoretical Perspective: Intersectionality and Covid-19 - Arivia, Gadis (Yayasan Jurnal Perempuan, 2020)
The author argues for using a new theoretical foundation and criticizes Gender Mainstreaming perspective in issues related to gender. The author proposes an intersectionality approach that can critically see the problem of Covid-19 and its implications to not only gender relations (men and women) but also race, ethnicity, class, LGBTQIA, and other minority groups. The author emphasizes the concept of critical praxis, which uses both critical questions and activism for total social change.